News Media Brand Equity in a New Media Environment - Saulite Linda (Economics and Business)
Digitalisation has profoundly altered how media are distributed and audiences consume media information, reshaping the media environment and introducing new competitors to media brands. This new media environment deludes media brand associations, contributing to an environment where audiences care less about content sources or brands of media. The younger audience, Generation Z, is an even more platform-on-demand and experience-driven audience. They favour social media and global media and care less about national media brands. Media consumption trends among youthful audiences have become crucial as the sector recognises this audience as a significant portion of the market today and signalling media consumption trends after coming generations. This study examines the impact of news media attributes and perceived uniqueness on news media brand equity in the new media environment. The study emphasises media brand distinctiveness and its effect on news media brand equity. The decision tree method is applied to predict the most significant news media attributes contributing to news media brand equity and the perceived uniqueness of the news media brand. Research results demonstrate the influence of content-consumption-related brand attributes and uniqueness on media brand equity.